Sodium Butyrate Supplementation for Improving Poultry and Rabbit Performance - Abd El-Aziz , A. H.; El-Sabrout, K.; Abo Ghanima, M. (Faculty of Animal Science, IPB University, 2024)
Sodium butyrate (SB) is a compound that belongs to the class of short-chain fatty acids (SCFA). It is derived from the breakdown of dietary fiber in the colon by gut bacteria. Supplementation of SB in poultry and rabbit diets is of great importance due to its numerous benefits to animal health and performance. Previous studies have shown that sodium butyrate can improve nutrient digestibility, enhance gut health, strengthen the immune system, and reduce the incidence of intestinal diseases in poultry. These favorable benefits eventually contribute to the increased of growth, feed efficiency, and profitability in the poultry and rabbit industries. By improving nutrient digestibility, enhancing gut health, and strengthening the immune system, SB supplementation helps to reduce the incidence of intestinal diseases in poultry and rabbits. This ultimately leads to improved growth, feed efficiency, and overall profitability in the poultry industry. Additionally, SB supplementation can help reduce the need for antibiotics in poultry farming, promoting a more sustainable and environmentally friendly approach to raising poultry. It has efficacy against acid-intolerant species, including Salmonella sp., Clostridium perfringens, and Escherichia coli. Furthermore, the pH of the gastrointestinal system was successfully decreased by administering SB. These properties make SB a promising alternative for maintaining gastrointestinal health and improving poultry and rabbit performance. Therefore, this review provides insight into the continuous development of novel SB supplements and highlights their potential contribution to poultry and rabbit farms.